KAJIAN PROSES EKSTRAKSI ION LOGAM Cu(II) DAN Co(II) DENGAN EKSTRAKTAN 1-fenil-3-metil-4-stearoilpirazol-5-on (HPMSP) (STUDY ON THE EXTRACTION OF Cu(II) AND Co(II) WITH 1-phenyl-3-methyl-4-stearoylpyrazol-5-one (HPMSP) - Kusrijadi, Ali; Sonjaya, Yaya; Sunarya, Yayan (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2002)
The extraction of Cu(II) and Co(II) with 1-phenyl-3-methyl-4-stearoylpyrazol-5-one (HPMSP) as the chelating ligandÂ using chloroform solvent have been studied. The extraction mechanism of Cu(II) and Co(II) and the composition of extracted species has been determined. Cu(II) and Co(II) was extracted as Cu(PMSP)2 and Co(PMSP)2. The effect of concentration HPMSP and pH has also been investigated.